2005
DOI: 10.1080/10241220600628640
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric study of methyl methacrylate-alcohol mixtures by Time Domain Reflectometry at 293 K

Abstract: Using picosecond Time Domain Reflectometry (TDR), dielectric relaxation studies have been carried out on binary mixtures of methyl methacrylate with 1-propanol, 1-butanol, 1-heptanol and 1-octanol for various concentrations over the frequency range from 10 MHz to 10 GHz at 293 K. The Kirkwood correlation factor and excess inverse relaxation times were determined and discussed to yield information on the molecular structure and dynamics of the mixture. The static permittivity and relaxation time decrease with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 18 publications
3
22
0
Order By: Relevance
“…Also, it is found that in the alcohol-rich region, the dielectric parameters for the mixtures increases, whereas when the concentration of MA dominates in the mixture, the dielectric parameters decreases. Similar conclusions were drawn by Sivagurunathan et al for methyl methacrylate -alcohols 23 binary mixtures.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Also, it is found that in the alcohol-rich region, the dielectric parameters for the mixtures increases, whereas when the concentration of MA dominates in the mixture, the dielectric parameters decreases. Similar conclusions were drawn by Sivagurunathan et al for methyl methacrylate -alcohols 23 binary mixtures.…”
Section: Resultssupporting
confidence: 76%
“…Chaudhari et al 5 reported the dielectric parameters for butyl acetate-alcohol mixtures using the time domain technique. Recently our research group has investigated the complex formation of alkyl methacrylates with proton donors (primary alcohols) using FTIR spectroscopic [6][7][8][9][10][11][12][13][14][15][16] technique. The aim of the present investigation is to study the molecular interaction in methyl acrylate-alcohol mixtures in the microwave region (10 MHz to 10 GHz) with varying concentrations (0% to 100%) using TDR technique for temperatures ranging from 283 K to 313 K. The relaxation behaviors of these mixtures were explained by the Debye model.…”
Section: Introductionmentioning
confidence: 99%
“…The values of excess inverse relaxation time is negative over entire concentrations of 2-BU and for all temperature indicate slower rotation of dipoles. 2,3,29 This is due to dipole-dipole interaction (chlorine group (-Cl) of AC and carbonyl group (C=O) of 2-BU) produces a field in such way that the effective dipoles rotation is hindered. The plot of excess molar volume (V E ) of binary mixtures is shown in Fig.…”
Section: 2728mentioning
confidence: 99%
“…The dielectric relaxation behaviour of mixtures of polar molecules under varying conditions of compositions is very important as it helps in obtaining information about relaxation process in mixtures. There have been several investigations on the dielectric behaviour of solvent mixtures in which dielectric relaxation spectra have been used to examine molecular orientations, hydrogen bonded networks, and microdynamics of these systems [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%